SPECT/CT in Postoperative Hand and Wrist Pain - Strobel, Klaus; Van Der Bruggen, Wouter; Hug, Urs; Gnanasegaran, Gopinath; Kampen, Willm Uwe; Kuwert, Torsten; Paycha, Frederic; Van Den Wyngaert, Tim (Seminars in Nuclear Medicine, 2018)
In this review we summarize the current evidence and experience regarding the performance of SPECT/CT in the evaluation of patients with postoperative painful wrist or hand. There is a wide range of operative wrist and hand interventions due to congenital, traumatic, degenerative, or inflammatory diseases. A significant number of patients suffer from pain after operative procedures. Several imaging modalities have been used to evaluate the reason for painful postoperative wrists like standard conventional x-rays, ultrasound, CT, MRI, or bone scintigraphy. In the last decade, bone SPECT/CT has offered a new approach in combining metabolic and morphologic cross-sectional information in patients with painful postoperative wrists and is increasingly used if standard imaging fails to identify the pain generator. SPECT/CT is less hampered by artifacts caused by metallic implants and shows more details of the cortical bone compared with MRI. MRI is generally superior regarding visualization of soft tissue structures like tendons, synovia, cartilage, muscles, and ligaments. SPECT/CT arthrography has been established to enable the assessment of cartilage and ligament tears.
EVALuna2:212299